2022
DOI: 10.3390/universe8020111
|View full text |Cite
|
Sign up to set email alerts
|

Milky Way Star Clusters and Gaia: A Review of the Ongoing Revolution

Abstract: The unprecedented quality of the astrometric measurements obtained with the ESA Gaia spacecraft have initiated a revolution in Milky Way astronomy. Studies of star clusters in particular have been transformed by the precise proper motions and parallaxes measured by Gaia over the entire sky as well as Gaia’s deep all-sky photometry. This paper presents an overview of the many topics of cluster science that have been impacted by the Gaia DR1, DR2, and EDR3 catalogues from their release to the end of the year 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 303 publications
1
22
0
Order By: Relevance
“…Limited by Galactic dust extinction and field-star contamination, the identification of cluster members and the establishment of complete cluster samples are a difficult task. However, Gaia satellite (Gaia Collaboration et al 2016) observations have yielded a large amount of stellar data with accurate astrometric measurements (Gaia Collaboration et al 2018a, 2021, and many studies based on these data have revealed a huge increase in the number of identified star clusters (Cantat-Gaudin 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited by Galactic dust extinction and field-star contamination, the identification of cluster members and the establishment of complete cluster samples are a difficult task. However, Gaia satellite (Gaia Collaboration et al 2016) observations have yielded a large amount of stellar data with accurate astrometric measurements (Gaia Collaboration et al 2018a, 2021, and many studies based on these data have revealed a huge increase in the number of identified star clusters (Cantat-Gaudin 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Differently to asterisms or field stars along a given line of sight, the member stars of a cluster have the same characteristics in terms of spatial and kinematic locations; this allows stellar aggregates to be found by clustering based on astrometric data (Castro-Ginard et al 2018;Liu & Pang 2019). Up to now, the majority of new clusters were detected through the DBSCAN clustering algorithm (e.g., Castro-Ginard et al 2020, 2022He et al 2021He et al , 2022 and its improved method HDBSCAN (e.g., Kounkel & Covey 2019;Hunt & Reffert2021). DBSCAN has been demonstrated to be a very efficient blind search method in big-data approaches (Gao et al 2014;Cantat-Gaudin 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In this work we are reporting distant open clusters (older tan 1.2 Gyr) instead of single stars, as shown in most of the papers referred above. A recent review of the spatial distribution of star clusters and the impact of the subsequent releases of Gaia data on the topic can be found in Cantat-Gaudin (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Limited by Galactic dust extinction and field star contamination, the identification of cluster members and the establishment of complete cluster samples are a difficult task. However, Gaia satellite (Gaia Collaboration et al 2016) observations have yielded a large amount of stellar data with accurate astrometric measurements (Gaia Collaboration et al 2018a, 2021, and many studies based on these data have brought a huge increase in the number of identified star clusters (Cantat-Gaudin 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Kounkel & Covey 2019;Hunt & Reffert 2021). DBSCAN has been demonstrated to be a very efficient blind search method in big-data approaches (Gao et al 2014;Cantat-Gaudin 2022).…”
Section: Introductionmentioning
confidence: 99%